The New Era of Life Order In The COVID-19 Pandemic Condition On The Organizational Performance Of Regional Technical Implementation Unit For The Management Cidurian-Cisadane Watershed - Risnawati Risnawati; Ira Irawati; Nandang Alamsah Deliarnoor; Heru Nurasa (Aliansi, 2022)
The purpose of this study is to be able to analyze the performance of organizations published by researchers in Indonesia by strengthening articles managed by research sources during the Covid-19 pandemic which has an impact on data collection that cannot be directly spacious because it is constrained by the Covid-19 pandemic, but in this way the researcher can process the data obtained from the researchers into several categories, including research titles, abstracts, and keywords based on organizational performance. focus. In the organizational structure of the Banten Provincial Public Works and Spatial Planning Office, there are Regional Technical Implementation Units (UPTD) that manage technical work in the field, one of which is the Regional Technical Implementation Unit (UPTD) Cidurian - Cisadane Watershed Management (DAS), where the population density level is quite a lot and the work area is quite heavy with a fairly high performance with the Covid-19 performance in the Regional Technical Implementation Unit (UPTD) Cidurian - Cisadane for the Watershed Management (DAS) experiencing good indicators that were previously not achieved with the national disaster Covid-19 employee performance cannot be surveyed and fielded, therefore in the new life order in the Covid-19 pandemic conditions, the UPTD Regional Technical Implementation Unit for the Management of the Cidurian - Cisadane Watershed (DAS) can adjust conditions by maintaining the Health protocol.